The Influence of Individual Differences in Students on the Learning Process and Outcomes - Annisa Rafifah Nabilah; Aysha Fajrin; Aziziyah Mabruroh; Azzura Chader Sultan; Dessy Kurnia Wati; Muhammad Sayuti (Feelings: Journal of Counseling and Psychology, 2026)
Each student has different characteristics from one another, both in terms of intellectual ability, learning motivation, learning style, family and social background, and learning readiness. These individual differences are an unavoidable reality in education and have a significant impact on the learning process and outcomes of            students. This article aims to describe the concept of individual differences among students, the factors that cause these differences, and their influence on the learning process and learning outcomes. The research method used is descriptive qualitative with a literature study approach, which is to examine and analyze various relevant literature sources, such as scientific journals related to psychology, education, and individual differences in learning. The results of the study show that individual differences affect the speed of learning, how students understand the material, their response to learning methods and media, and their learning outcomes in cognitive, affective, and psychomotor aspects. Learners with different characteristics require different learning and evaluation approaches. Therefore, teachers are required to understand the individual  differences  of  learners and  apply  varied  and differentiated learning strategies, as well as fair and continuous evaluation, so that the learning process can run effectively and optimize the potential of each learner.